Ageing, Care Need and Quality of Life The Perspective of Care Givers and People in Need of Care - Doblhammer, Gabriele; Scholz, Rembrandt; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2010)
Increasing life expectancy and population ageing leads to a rising number of elderly people in need of care. Improvements in health may counterbalance this trend to some extent but cannot fully compensate it. In this proceedings, Gabriele Doblhammer and Rembrandt Scholz present combined expertise in the field of health, care need and care resources. Various care need projections based on diverse projection methods give a detailed overview on probable future developments of the number of people in need of care, mainly for Germany. A special emphasis is put on the future number of people with dementia in Germany. Next to that the authors explore past trends in health and care need in relation to increases in life expectancy and discuss the effects of sex, smoking, obesity, and other determinants that influence health and care need in older ages. The trends in health and care need are additionally viewed in relation to trends in the number of care need providers and their quality of life. This book is a valuable reference for academics in the social sciences, especially those with a focus on health care and demography and for practitioners in the field of health care.
Projections of Care Need and Care Resources -- People in Need of Long-term Care: The Present and the Future -- Care Need Projections for Germany until 2050 -- Care Need Projections by Marital Status and Childlessness for Germany 2000-2030 based on the FELICIE Project -- Projection of Care Need and Family Resources in Germany -- Cohort Trends in Disability and Future Care Need in Germany -- Projections of the Number of People with Dementia in Germany 2002 Through 2047 -- Health Factors and Care Determinants -- The Effect of Sex, Obesity and Smoking on Health Transitions: A Statistical Meta-analysis -- Demand for Long-term Residential Care and Acute Health Care by Older People in the Context of the Ageing Population of Finland -- Old Age, the Need of Long-term Care and Healthy Life Expectancy -- Trends in Individual Trajectories of Health Limitations: A Study based on the German Socio-Economic Panel for the Periods 1984 to 1987 and 1995 to 1998 -- Care Givers -- Perceived Care Giver Burden of Spouses and Children in Flanders: Who s Feeling more Burdened and Why? -- Voluntary Care Giving in the Life Course of Women in Eastern and Western Germany.
Keywords: Social sciences; Sociology; Social Sciences; Sociology; Sociology